Saving liberalism from itself : the spirit of political participation - Stacey, Timothy (Bristol University Press, 2022)
In the wake of populism, Timothy Stacey's book critically reflects on what is missing from the liberal project with the aim of saving liberalism. It explains that populists have harnessed myth, ritual, magic and tradition to advance their ambitions, and why opponents need to embrace rather than eschew them.